Administrasi Publik, Pembangunan dan Kemajemukan Etnis - Sofian Efendi (Magister Ilmu Administrasi Publik, 1999)
The appalling aftermath of massive riots in Indonesia during the crisis has, in a way, reflected the inability of public administration to be an intermediary between the state and the people in a multi-ethnic society. The lack of concern of public administration on the issues of muti-ethnicity is very obvious if one observe the limited number of articles or research on ethnic conflicts and the bureaucratic politics. Most of public administration literatures assumed an ideal society which consist of individuals who can be segregated only based on age, gender, occupation and economic class, without acknowledging race, culture, and religion. There are two course of actions to be considered to improve the capability of public administration in the process of intermediary and resolving the issue of multi-ethnicity, namely: proportional representation and affirmative action. The first is when the public administrators must consider recruitment process based on ethnic representation in the society. The second is when the public decision makers would have to take affirmative actions to allocate resources and funds to the various target groups given the fact that public policies and programs tend to create gainers and loosers in the society.